HMGB1 blood levels and neurological outcomes after traumatic brain injury: Insights from an exploratory study - Irma Wati Ngadimon; Devi Mohan; Mohd Farooq Shaikh; Ching Soong Khoo; Hui Jan Tan; Yu Mey Lee; Nor Syazwani Chamhuri; Farizal Fadzil; Nursyazwana Zolkafli; Alina Arulsamy; Jegan Thanabalan; Angel Aledo‐Serrano; et al. (Epilepsia Open)
Abstract Objective Posttraumatic epilepsy (PTE) and cognitive impairment are severe complications following traumatic brain injury (TBI). Neuroinflammation likely contributes, but the role of specific inflammatory mediators requires clarification. High‐mobility group box 1 (HMGB1) is an inflammatory cytokine released after brain injury that may be involved. This prospective longitudinal study investigated whether serum HMGB1 levels are associated with PTE development and cognitive decline over 12 months post‐TBI. Methods Serum samples were collected from 41 TBI patients, including mild and moderate to severe, at baseline, 6, and 12 months following TBI. HMGB1 was quantified by ELISA alongside interleukin‐1β (IL‐1β) and tumor necrosis factor (TNF). Cognitive assessments using validated neuropsychological assessments were performed at 6 and 12 months. The occurrence of PTE was also tracked. Results HMGB1 remained elevated at 12 months post‐TBI only in the subgroup (n = 6) that developed PTE (p = 0.026). PTE was associated with moderate to severe TBI cases. Higher HMGB1 levels at 12 months correlated with a greater decline in Addenbrooke's Cognitive Examination scores (p < 0.05). Reductions in HMGB1 (p < 0.05), IL‐1β (p < 0.05) and TNF (p < 0.001) levels from 6 to 12 months correlated with improvements in cognitive scores. Multivariate regression analysis confirmed that HMGB1 level changes were independently associated with cognitive trajectory post‐TBI (p = 0.003). Significance The study highlights the importance of understanding the interactions between HMGB1 and inflammatory markers in posttraumatic neuroinflammatory responses. Targeting HMGB1 and associated markers may offer a promising strategy for managing chronic neuroinflammation and mitigating cognitive deficits in TBI patients, emphasizing the potential for targeted therapeutic interventions in this context. Plain Language Summary This study examines how a protein called HMGB1 may contribute to epilepsy and cognitive deficits after traumatic brain injury (TBI). Patients with higher HMGB1 levels were more likely to develop epilepsy and experience significant cognitive decline within a year. Reducing HMGB1 and related inflammation was associated with better cognitive function and overall brain health. These findings suggest that HMGB1 could be a valuable marker and a potential target for treatments to prevent epilepsy and improve brain recovery after TBI.